Securitization : The Road Ahead - Segoviano, Miguel (Staff Discussion Notes; Staff Discussion Notes, 2015)
The discussion in this note seeks to preserve the beneficial features of securitization while mitigating those that may pose risks to financial stability. A comprehensive set of reforms-targeting both supply- and demand-side inefficiencies-will be needed to put securitization back on a sound, growth-supportive footing. The note departs from others in proposing a broad suite of principles applicable to various elements of the financial intermediation chain. After indentifying where policy makers have already made progress, we then propose measures to address remaining impediments to the rehabilitation of securitization markets. We also encourage more consistent industry standards for the classification of risk (albeit applied at a granular rather than overarching level). Finally, we introduce various initiatives that could aid in fostering the development of a diversified non-bank investor base for securitization in Europe.